Behavioral pharmacology of designer cathinones: a review of the preclinical literature - Gregg, Ryan A. (2013)
“Bath salts” is one street name for a family of synthetic cathinones that display pharmacological effects resembling cocaine and commonly abused amphetamines. Despite extensive legislation aimed at the criminalization of bath salts, several designer cathinones are gaining a foothold in the illicit drug scene; for example, in the United Kingdom, mephedrone (4-methylmethcathinone, MEPH) is highly popular among drug abusers whereas, in the United States, MDPV (methylenedioxypyrovalerone) and methylone are highly prevalent. To date, knowledge about the hazards of designer cathinones is based mostly on hospital reports and anecdotal evidence derived from online surveys. Despite the paucity of preclinical studies directed toward designer cathinones, a number of invaluable findings arising from those studies are enabling scientists to develop their neuropharmacological profiles. Despite their commonalities in chemical structures, synthetic cathinones possess distinct neuropharmacological profiles and produce different behavioral effects, including unique effects on locomotor activity, learning, anxiety, thermoregulation, and abuse liability. The present review will discuss the behavioral effects of MEPH, MDPV, and methylone and compare those effects to established psychostimulant drugs. The rise in the use of designer cathinones in the United States and abroad justifies further investigations into these compounds, both for a greater understanding of the danger that “bath salts” pose to the public, and to provide insight into replacement cathinones as they emerge onto the market.